Metabolic cycling in control of glucose-stimulated insulin secretion - Jensen, Mette V. (American Physiological Society, 2008)
Glucose-stimulated insulin secretion (GSIS) is central to normal control of metabolic fuel homeostasis, and its impairment is a key element of β-cell failure in type 2 diabetes. Glucose exerts its effects on insulin secretion via its metabolism in β-cells to generate stimulus/secretion coupling factors, including a rise in the ATP/ADP ratio, which serves to suppress ATP-sensitive K(+) (K(ATP)) channels and activate voltage-gated Ca(2+) channels, leading to stimulation of insulin granule exocytosis. Whereas this K(ATP) channel-dependent mechanism of GSIS has been broadly accepted for more than 30 years, it has become increasingly apparent that it does not fully describe the effects of glucose on insulin secretion. More recent studies have demonstrated an important role for cyclic pathways of pyruvate metabolism in control of insulin secretion. Three cycles occur in islet β-cells: the pyruvate/malate, pyruvate/citrate, and pyruvate/isocitrate cycles. This review discusses recent work on the role of each of these pathways in control of insulin secretion and builds a case for the particular relevance of byproducts of the pyruvate/isocitrate cycle, NADPH and α-ketoglutarate, in control of GSIS.